Comprehensiveness of Pediatric Antiepileptic Prescribing in Clinic Letters: Are We Communicating Well? - Butler, Christopher J.; Babiker, Mohamed O. E. (Journal of Pediatric Epilepsy, 2017)
This study aims to determine the comprehensiveness of pediatric epilepsy outpatient clinic letters in a tertiary pediatric neurology center with particular focus on the prescribing instructions. A retrospective study was conducted for all pediatric outpatient epilepsy clinic letters between August and October 2016. This study was undertaken in a tertiary pediatric neurology department at the Bristol Royal Hospital for Children, United Kingdom. A total of 160 patients were identified during the time period and included in the study. Letters were evaluated for the following information: patient demographics, inclusion of problem list, and medication details including the clarity of prescribing instructions. The comprehensiveness of letters was scored out of nine based on the nine categories; weight, diagnosis list, medication list, dose in milligrams, dose equivalence in milligrams/kilograms/day, formulation, strength or concentration of medication, if applicable is the volume of medication provided and is the trade name provided. A total of 94% of letters had a diagnosis or problem list provided which was clear. Only 68% letters had a separate medication list provided. The dose of antiepileptic drugs (AEDs) in milligrams was provided in 95% of letters. The formulation of the AED was provided in only 30% of letters. Only 24% of letters where a category 1 AED was prescribed had the trade name provided. This study has demonstrated significant omissions from outpatient pediatric epilepsy letters. The omissions presented in this study may culminate in inefficient communication and increased morbidity. We share practice improving learning points for writing comprehensive letters which we believe can be generalized to other pediatric specialties.
Keywords: outpatient letter; epilepsy; antiepileptic drugs; prescribing; pediatrics